The Pengaruh Transformational Leadership dan Quality of Work Life Terhadap Organizational Citizenship Behavior (OCB) Dimediasi Commitment Organizational Pada PT Rumah Bersama Seluler - Fathehah, Vannesya Alif Nur; Subiyanto, Didik; Yulianto, Eko (Universitas Hamzanwadi, 2025)
The current era of globalization increases competition in increasingly competitive companies and requires companies to improve innovation. The purpose of this study is to analyze the influence of transformational leadership and quality of work life on Organizational Citizenship Behavior (OCB) with organizational commitment as a mediating variable in PT Rumah Bersama Seluler. This study uses a quantitative approach with data collected through questionnaires. The research sample includes all employees of PT Rumah Bersama Seluler, which is 98 respondents. The results of the analysis of this study show that all hypotheses are accepted, namely transformational leadership and quality of work life affect organizational commitment and organizational citizenship behavior. The variable of organizational commitment also affects organizational citizenship behavior. This shows that employees who have a high quality of work life and organizational commitment, can increase employee OCB. The implications of this study are important for PT Rumah Bersama Sellular in increasing the role of OCB employees by increasing these factors